The Research Analysis of Environmental Issues in the Light of Maxims of Islamic Jurisprudence - Abdur Rahim; Khan, Janas; Ahmad, Rashid (Journal of Islamic and Religious Studies, 2021)
The regularity jurisprudence refers to maxims meant to integrate and resolve miscellaneous social problems according to Sharī‘ah. Later, in the light of the same, newly emerged issues are also settled. These maxims, once laid down, serve as Reference Guide, employed by Muftīs and Jurists in their edicts and verdicts, of which none are independent. Today both human and animal life is under threat from the dangerous effects of environmental pollution. Since it's a serious problem, therefore, much has been written on the ecosystem and its preservation. It's mentioned here as to how these environmental problems can be resolved in the light of the Holy Qur’ān and Sunnah. As Dr. Yūsuf al Qaraḍāwī, has provided guidance in his book “Ri’āyah al Bī’ah fī Sharī’ah al Islām” towards solving environmental problems through the regulations of Islamic jurisprudence, but he has just quoted a few jurisprudential regulations without implementations on environmental problems. This research, analytically and narratively, is an effort to find an answer to the question: What is the role of the regulations of Islamic jurisprudence in the newly emerging issues of the day, especially environmental issues? This research shows the solution to the environmental crisis through the regulations of Islamic jurisprudence.